A new species of the Simulium (Gomphostilbia) (Diptera: Simuliidae) from Thailand, with its phylogenetic relationships with related species in the Simulium asakoae species-group - Srisuka, Wichai; Takaoka, Hiroyuki; Fukuda, Masako; Otsuka, Yasushi; Saeung, Atiporn (Elsevier, 2019)
A new species of black fly, Simulium (Gomphostilbia) rampae, is described, based on adult male, its pupal exuviae and mature larvae collected from Doi Inthanon National Park, northern Thailand. This new species is placed in the Simulium asakoae species-group, and is characterized in the male by the high number of upper-eye facets in 17 vertical columns and 18 horizontal rows, in the pupa by the gill with a long common basal stalk, cone-shaped terminal hook, and cocoon with an anterodorsal projection, and in the larva by the medium-long postgenal cleft. A DNA analysis using COI gene supported its assignment to the S. asakoae species-group and showed its close relationship to S. (G.) udomi Takaoka & Choochote and S. (G.) chiangdaoense Takaoka & Srisuka. This is the fourth member of the S. asakoae species-group recorded from Thailand. © 2019 Elsevier B.V.